Atom, Ion, Molekul dan Interaksinya: Analisis dan Perhitungan Mekanika Kuantum ab Initio - Siahaan, Parsaoran (Chem Info Journal, 2013)
The widely explanation of the regularly atomic ionization energy properties by element periodic system, quantum theory and Schrodinger equation is still opened to be developed and explained for understanding the whole inherently properties of the elements and molecules. Developing of Â the theory even also enable us to explain the nanoparticle elements properties, or to explain the non-covalent interactions properties of compounds. This developing will have been doing by computation method of quantum theory ab initio which is able to predict every hypotetic atomic, molecule, and its cluster.